A Lubrication Theory for Anisotropic Slips and Flow Rheology. Issue 2 (3rd March 2016) - Jao, Hsiang-Chin; Chang, Kuo-Ming; Chu, Li-Ming; Li, Wang-Long
Abstract: A lubrication theory, considering the coupled effects of anisotropic slip on both the solid–liquid interface and non-Newtonian power law lubricant, is proposed to enhance surface treatment and oil additives. A modified Reynolds equation as well as Poiseuille and Couette flow rate correctors are then derived by applying the rheology model and Navier slip boundary conditions with orthogonal principal slip lengths (, ). Hence, the different slenderness ratios that lead to different performance of journal bearings are used to highlight the coupling effects of anisotropic slips and flow rheology. Contours of constant load ratios are plotted and then the parameters in flow rheology and boundary slip can be located while designing functional surfaces in journal bearings.